Media coverage and resources from the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series - Albinati, Chris; Bonin-Labelle, Geneviève; Buddle, Kathleen; Gagnon, John; King, Gretchen (Université d'Ottawa | University of Ottawa, 2017)
Media coverage information, participation documentation and resources for the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence Conference and Outreach events
Keywords: First Nations; Inuit; Métis; Broadcasting; Policy; CRTC